Huella ecológica y biocapacidad de la población, como indicadores de sostenibilidad, en la ciudad de Portoviejo - Alarcón Mendoza, Wendy Virginia (2021)
The Ecological Footprint (HE) and Biocapacity (BC) are sustainability indicators, expressed in units of global hectares. Portoviejo city has approximately 246,003 inhabitants, who make up a potential group dependent on territories that assimilate their waste and produce natural resources to satisfy their needs. In this regard, the objective of this research was to calculate the ecological footprint and biocapacity to determine the city's sustainability. Applying the compound method of Wackernagel and Rees (1996), the calculation of the ecological footprint was performed, achieving a value of 0.553 hectares per person per year and a biocapacity of 0.3622 hectares per capita per year, resulting that Portoviejo city has an ecological deficit. Based on this, were proposed public policies adapted from Franco's (2013) and Cárdenas's (2018) methodology to improve urban environmental management: environmental education, incentives for the use of sustainable alternatives, and inter-institutional articulation. In the public policy proposal, it was advised to implement the recommendations about environmental education, and inter-institutional articulation, because they are budgetary, legal, and environmentally viable. On the contrary, the advice of incentives for the use of sustainable alternatives is discarded due to their high investment cost.